Complete response of advanced hepatocellular carcinoma to sorafenib : another case and a comprehensive review - Kim, Tae Suk; Kim, Ji Hoon; Kim, Baek hui; Lee, Young-Sun; Yoo, Yang Jae; Kang, Seong Hee; Suh, Sang-June; Jung, Young Kul; Seo, Yeon Seok; Yim, Hyung Joon; Yeon, Jong Eun; Byun, Kwan Soo (Clinical and molecular hepatology, 2017)
Since sorafenib was introduced in 2007 for treating advanced hepatocellular carcinoma (HCC), 15 patients have achieved a complete response (CR) in advanced HCC. However, only four of these reports can be regarded as real CRs involving adequate assessments including imaging, serum tumor markers, and histologic examinations of completely resected specimens. A 54-year-old man with hepatitis C virus (HCV)-related liver cirrhosis (LC) presented to our unit. A CT scan demonstrated a 3.8-cm arterial hypervascular/portal-washout mass in the right lobe and invasion in the right portal vein. Twelve weeks after beginning sorafenib therapy, the AFP level was normalized and a CT scan showed a prominent decrease in the hepatic mass and a significant decrease in the volume of portal vein thrombosis (PVT). The patient received a right liver hemihepatectomy after 12 months. No viable tumor cells were found in the resected specimen, and there was no thrombotic obstruction of the portal vein. Twelve months later the patient showed no clinical evidence of HCC recurrence. This is the first case of CR in HCC treatment following sorafenib with histologically confirmed HCV-related HCC without LC evidence, HCC with PVT, and a follow-up of longer than 12 months. This case seems to be an extremely unusual clinical outcome in advanced HCC.